High-pressure optical floating-zone growth of Li2FeSiO4 single crystals - Hergett, Waldemar; Neef, Christoph; Wadepohl, Hubert; Meyer, Hans-Peter; Thauer, Elisa; Klingeler, Rüdiger (Journal of crystal growth, 2019)
We report the growth of mm-sized Pmnb-Li2FeSiO4 single crystals by means of the optical floating-zone method at high argon pressure and describe the conditions required for a stable growth process. The crystal structure is determined and refined by single-crystal X-ray diffraction. The lattice constants amount to a=6.27837(3) Å, b=10.62901(6) Å and c=5.03099(3) Å at 100K. In addition, we present high-resolution neutron powder diffraction data that suggest that the slight Li - Fe site exchange seems to be intrinsic to this material. High quality of the crystal is confirmed by very sharp anomalies in the static magnetic susceptibility and in the specific heat associated with the onset of long-range antiferromagnetic order at TN=17.0(5) K and pronounced magnetic anisotropy for the three crystallographic axes. Furthermore, magnetic susceptibility excludes the presence of sizable amounts of magnetic impurity phases.
Die Zahlen "2" und "4" sind im Titel tiefgestellt
Available online: 12 March 2019
Gesehen am 16.04.2019